Lingkungan Hidup dalam Naskah Wawacan Ogin Amar Sakti - Ruhaliah, Ruhaliah (Masyarakat Pernaskahan Nusantara, 2022)
This article is written as a result of the study of meaning of Sundanese manuscript of a folklore titled Wawacan Ogin Amar Sakti. The study was conducted based on story’s settings and structural approach. The purpose of this study was to reveal the contribution of story’s meanings towards humanity’s environmental quality. This study utilized descriptive comparative methods, while the data collection used documentation study. The findings are in the form of interpretations concluded based on the results of data analysis results found in the text as well as its comparison with data found in other relevant sources. Based on the data analysis results, it can be concluded that the story setting elements found in Ogin Amar Sakti script is environmental/ecosystem transmission or inheritance vehicles; those are (1) to not to cut down, pollute, or turn dense forests as covert for evil deeds, (2) to look after and maintenance mountains and forests as they embody various resources, (3) to not turn forests into hunting ground for animals, and (4) to arrange settlements as delightful and pleasing place. These messages are in line with other texts and symbols such as folklore and gunungan, as well as become concrete foundation for environmental preservation and food security strategy. === Tulisan ini merupakan hasil kajian makna atas cerita naskah berbahasa Sunda Ogin Amar Sakti. Kajian dilakukan atas unsur latar cerita (setting), menggunakan pendekatan struktural. Pengkajian dilakukan dengan tujuan untuk mengungkap kontribusi makna cerita bagi kualitas lingkungan hidup manusia. Metode yang digunakan ialah metode deskriptif komparatif. Teknik pengumpulan datanya ialah teknik studi dokumentasi. Temuan-temuan berupa tafsiran disimpulkan berdasarkan hasil analisis data yang terdapat dalam teks serta melalui perbandingannya dengan data yang terdapat dalam sumber lain yang relevan. Berdasarkan hasil analisis data dapat disimpulkan bahwa unsur latar cerita naskah Ogin Amar Sakti merupakan wahana transmisi atau pewarisan lingkungan hidup (ekosistem), yaitu (1) hutan lebat jangan ditebang, dikotori, dijadikan tempat menyembunyikan perbuatan jahat, (2) awasi dan pelihara gunung-gunung dan hutan karena mengandung aneka kekayaan, (3) hutan jangan dijadikan lahan perburuan satwa, dan (4) lakukan penataan pemukiman menjadi tempat yang menyenangkan dan membahagiakan. Amanat mengenai pelestarian hutan tersebut sejalan dengan teks dan simbol lain, di antaranya cerita rakyat dan gunungan, serta menjadi landasan konkret bagi peletarian lingkungan hidup dan strategi ketahanan pangan.